ARABIC-THE METHODOLOGY ADOPTED BY SHEIKH AL-SHANQEETI IN EXPLAINING THE RELIANCE ON HADITHS IN HIS INTERPRETATION OF “ADWAA AL-BAYAN” AN ANALYTICAL STUDY - Ihsan Ulhaq; Abdul Samad Shaikh (دی اسکالر)
Shaikh Shanqīṭī has been well known for his Encyclopedic, versatile, and scholarly personality. He has contributed in almost every field of Islamic studies, from Tafsīr, ʾUṣūl al-Tafsīr, Ḥadīth, Muṣṭalah al-Ḥadīth, Fiqh and ʾUṣūl al-Fiqh to ʿIlm al-Kalām. He has been famously known for His commentary on Quran named: “ʾAḍwāʿ al-Bayān fī Tafsīr al-Quran bi al-Quran” which is considered one of the best commentaries on the interpretation of Quran with the Quran. Although, this aspect has been considered by other commentators, interpreting every ʾāyah being restricted within the Quranic context, is the salient feature of this commentary. Another aspect that needs to be highlighted from this Tafsīr is the approach of Shaikh Shanqīṭī to consider a Ḥadīth reliable. He is the unique in applying this method in a way that he considers many things to strengthen a Ḍaʿīf Ḥadīth (weak) so be reliable. by doing this, he considers other branches of Islamic Studies playing their role in the process of Ḥadīth authentication. In fact, this approach is different from Muḥaddithīn (Ḥadīth scholars), who usually consider only ʾIsnād (chain of transmitters) to strengthen a Ḍaʿīf Ḥadīth. In this article, we will be trying to explore this aspect and highlight all those standards that can be considered to strengthen a Ḍaʿīf Ḥadīth from the perspective of Shaikh Shanqīṭī.